Immune factors and health of Antarctic explorers - D. Zabara; I. Kozeretska; I. Deineko; Ya. Anoshko; N. Shapovalenko; L. Stamboli; B. Dons’koi (Ukrainian Antarctic Journal, 2021)
The immune system plays a major role in human homeostasis, yet a body’s unique individuality complicates the diagnostic forecasting of unfavourable physiological states and diseases. Studying the immunophenotypic features of winterers of the Ukrainian Antarctic Expeditions before, during, and after their assignments might shed some light on the possible place of immune accentuations in the development of certain physiological states. To determine the natural-killer (NK) cytotoxicity and the immunophenotype in 52 applicants who wanted to take part in an expedition and nine participants who had come back, we used flow cytofluorometry. Blood serum samples taken before, during, and after the expeditions were also tested for hormones, anti-infective, anti-parasitic, and autoimmune antibodies. The high absolute and relative numbers of NK lymphocytes, high NK cytotoxicity, and high expression of HLA-DR on the CD3+CD8+ lymphocytes were correlated with a person’s unfavorable health status during the expedition. In Antarctica, cortisol levels sharply increased, yet they normalized upon return. In most winterers, there were no significant health complications during the expeditions. Neither reactivated nor primary viral infections were registered, as well as clinical autoimmune ones. Upon return, the winterers had significantly lower leukocytes and lymphocytes and increased expression of activation markers (HLA-DR) on the T-cells. The found risk factors can characterize the polar researchers’ immunophenotypes yet require validation on larger samples. The expedition environment causes increased stress, entailing, however, neither clinical manifestations nor elements of immunosuppression. The polar researchers bear the consequences of the prolonged stress that inhibit leucopoiesis as late as six months after their return, which should be considered while reviewing applications for the next season.